Nocturnal Enuresis - Arni Arni; Tri Budiati; Mahamah Mahamah; Hafiz Abubakar; Rafita Ramayati; Rusdi Djas (Indonesian Pediatric Society, 1995)
From November 1, 1992, to February 1, 1993 a cross-sectional study was conducted on patients with nocturnal enuresis who attended to the Child Clinic of Dr. Pirngadi Hospital, Medan, with the age ranging from 4 to 15 years. All patients were interviewed by using questionnaires, and the physical and laboratory examinations were done. Enuresis is defined as an involuntary urination and occurring repeatedly in children of> 4 years, with the minimum of 2 times/month and no indicators of organic disturbances. Of the 168 patients with the age of 4 to 15 years, 70 (41.6%) were found with nocturnal enuresis; 38 (54.2%) were males and 32 (45.8%) females. Most of the patients 33 patients (4 7.1 %) were found in the age group of 4-5 years. All parents of the patients suggested that their children had enuresis without familial complaints because they believe that it would stop gradually with the increases in age. No significant difference was found in the socio-economic status between the enuretic and non-enuretic children. The two groups showed no significant differences in growth and urinary tract infection was not noted.